Breaking the silence: sexual coercion and abuse in post-conflict education - Bray-Watkins, S (Refugee Studies Centre, University of Oxford, 2019)
Experience from the Central African Republic makes clear that global efforts to increase numbers of children in school, particularly in conflict-affected areas and for displaced children, need to pay greater attention to safety and accountability.